Hope and Christian ethics - Elliot, David (New studies in Christian ethics, 2017)
The eudaimonia gap -- The theological virtue of hope in Aquinas -- Rejoicing in hope -- Presumption and moral reform -- Despair and consolation -- The problem of worldliness -- Hope and the earthly city